Comprehensive genomic profiling of extrahepatic cholangiocarcinoma reveals a long tail of therapeutic targets. Issue 5 (23rd October 2015) - Lee, Hwajeong; Wang, Kai; Johnson, Adrienne; Jones, David M; Ali, Siraj M; Elvin, Julia A; Yelensky, Roman; Lipson, Doron; Miller, Vincent A; Stephens, Philip J; Javle, Milind; Ross, Jeffrey S
Abstract : Aim: We queried whether extrahepatic cholangiocarcinoma featured clinically relevant genomic alterations that could lead to targeted therapy. Methods: Comprehensive genomic profiling by hybridisation capture of up to 315 genes was performed on 99 clinically advanced extrahepatic cholangiocarcinoma. Results: There were 60 male and 39 female patients with a median age of 60.5 years. A total of 400 alterations were identified (mean 4.0; range 0–13) in 84 genes. Eighty-two (83%) of extrahepatic cholangiocarcinoma patients featured at least one clinically relevant genomic alterations including KRAS (43%); ERBB2 (9%), PTEN (7%); ATM and NF1 (6%) and CCND1, FBXW7, GNAS, MDM2 and NRAS (all at 5%). BRAF, BRCA2, CDK4, CDK6, FGFR1, FGFR3, PTCH1, RAF1 and S TK11 were each altered in a single patient. No IDH1/2 mutations or FGFR2 gene fusions were identified. Conclusions: Comprehensive genomic profiling of extrahepatic cholangiocarcinoma differs significantly from intrahepatic cholangiocarcinoma and pancreatic adenocarcinoma, and reveals diverse opportunities for the use of targeted therapies.